Perceptions about Monetary Policy - Michael D. Bauer; Carolin E. Pflueger; Adi Sunderam (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate perceptions about the Fed's monetary policy rule from panel data on professional forecasts of interest rates and macroeconomic conditions. The perceived dependence of the federal funds rate on economic conditions is time-varying and cyclical: high during tightening episodes but low during easings. Forecasters update their perceptions about the policy rule in response to monetary policy actions, measured by high-frequency interest rate surprises, suggesting that forecasters have imperfect information about the rule. The perceived rule impacts asset prices crucial for monetary policy transmission, driving how interest rates respond to macroeconomic news and explaining term premia in long-term interest rates.
Keywords: E43; E52; E58; 330; FOMC; monetary policy rule; survey forecasts; beliefs